PENGARUH KENTUNTASAN PROSES PEMBELAJARAN, KOMPETENSI KELULUSAN TERHADAP KEPUASAN WALI MURID MI ADDINNIYAH MOJOKERTO - al anshori, Jakariya; Fadly Usman , Eng (ILJ: Islamic Learning Journal, 2023)
Basically every human being has the ability to learn. Such a process, this is natural from birth to growing up. The existence of a learning activity, can not be separated from the goals to be achieved. Competency standard is the minimum competency measure that must be achieved by students after following a learning process in a particular educational unit. The educational program is an effort to increase human resources, namely to provide a place for someone to develop their level of knowledge and skills in carrying out their duties and authorities in accordance with their work. Quantitative research is a research method used to examine certain populations or samples, data collection uses research instruments, data analysis is quantitative or statistical, with the aim of testing the established hypotheses.           In addition to the three independent variables used in this research, there is 0.015% which affects the customer in the decision of Walipupil MI ADDINIAH, Jiyu Village, Kec, Kutorejo Kab. Mojokerto which is not researched. So that further research is expected to add other variables in their research.